An evaluation of the innovative potentials of a HIV pilot exploring medical pluralism in rural South Africa - Christopher J. Burman (Taylor & Francis Group, 2018)
This article reflects on an internal evaluation undertaken to estimate the potentials of a community-university pilot project to be developed into a bonafide innovation that can be applied at scale. The focus of the community-university partnership has been to reduce the unintended consequences of medical pluralism on the HIV and AIDS epidemic in Waterberg district, Limpopo Province, South Africa. Despite promising outputs from the partnership - including an increase in adherence to antiretroviral therapy and a reduction in stigma among traditionalists living with HIV - the partnership wished to establish whether further funding should be applied for to take the pilot from its current prototype status to a more established innovation. In order to evaluate the innovative potentials of the pilot, the opportunity vacuum model of innovation was adapted and applied. The findings indicate that (1) the application of the opportunity vacuum model of innovation to evaluate the potentials of the pilot to be developed into a bonafide innovation was fit for purpose and (2) the pilot contains the key ingredients that are associated with innovations in the making. The discussion reflects on the social potentials of the pilot to contribute to 90-90-90 from a global, national and local perspective. The reflection concludes by suggesting that the opportunity vacuum model of innovation is a versatile heuristic that could be applied in other contexts and the community-university pilot represents a nascent innovation which has sufficient potential to justify further development.